Handbook of Response to Intervention The Science and Practice of Multi-Tiered Systems of Support - Jimerson, Shane R.; Burns, Matthew K.; VanDerHeyden, Amanda M. (Springer US : Imprint: Springer, 2016)
The Second Edition of this essential handbook provides a comprehensive, updated overview of the science that informs best practices for the implementation of response to intervention (RTI) processes within Multi-Tiered Systems of Support (MTSS) to facilitate the academic success of all students. The volume includes insights from leading scholars and scientist-practitioners to provide a highly usable guide to the essentials of RTI assessment and identification as well as research-based interventions for improving students' reading, writing, oral, and math skills. New and revised chapters explore crucial issues, define key concepts, identify topics warranting further study, and address real-world questions regarding implementation. Key topics include: Scientific foundations of RTI Psychometric measurement within RTI RTI and social behavior skills The role of consultation in RTI Monitoring response to supplemental services Using technology to facilitate RTI RTI and transition planning Lessons learned from RTI programs around the country The Second Edition of the Handbook of Response to Intervention is an essential resource for researchers, graduate students, and professionals/scientist-practitioners in child and school psychology, special and general education, social work and counseling, and educational policy and politics.